Obraz małego dziecka i jego wychowania w dziele Yconomica Konrada z Megenburga. Przyczynek do historii wychowania okresu późnego średniowiecza - Brzeziński, Witold (Biuletyn Historii Wychowania, 2018)
The paper is concerned with the views of the fourteenth-century German thinker and writer Conrad of Megenburg on the nature of a little child (until the age of seven) and his or her upbringing as reflected in his Yconomica. This work belonged to the oeconomica genre – books of instructions about the prudent management of the household, including recommendations on the proper upbringing of offspring. Conrad perceives the child primarily as lacking an ability to reason. Consequently, in his opinion what the child speaks or does is only a mindless imitation – a kind of aping – of what he or she hears or sees in others. Therefore, recommendations given by Conrad to parents on how they should take care of their children are mostly concerned with their health and proper physical development. To a lesser degree the first years of living is a time for the child to learn some good manners, e.g. while eating and to gain basic religious knowledge. This kind of learning, however, does not require any understanding, it consists in developing appropriate habits in children. Only when they reach the age of seven did their proper education begin. In his view of the little child and his or her upbringing Conrad of Megenburg follows the Aristotelian tradition.